2020
DOI: 10.1007/s00281-019-00777-w
|View full text |Cite
|
Sign up to set email alerts
|

Recent findings in the genetics and epigenetics of asthma and allergy

Abstract: In asthma and allergy genetics, a trend towards a few main topics developed over the last 2 years. First, a number of studies have been published recently which focus on overlapping and/or very specific phenotypes: within the allergy spectrum but also reaching beyond, looking for common genetic traits shared between different diseases or disease entities. Secondly, an urgently needed focus has been put on asthma and allergy genetics in populations genetically different from European ancestry. This acknowledges… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
70
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 116 publications
1
70
0
11
Order By: Relevance
“…Several studies have focused on overlapping or specific phenotypes within the allergy spectrum and beyond, looking for common genetic traits shared between different diseases or disease entities. Importantly, asthma and allergy genetics in populations genetically different from European ancestry have been addressed, being key as the majority of new asthma patients are not white [4]. In epigenetics, several large-scale epigenome-wide association studies (EWAS) have been performed and interaction between environment and epigenetic signatures were of focus.…”
Section: Prefacementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have focused on overlapping or specific phenotypes within the allergy spectrum and beyond, looking for common genetic traits shared between different diseases or disease entities. Importantly, asthma and allergy genetics in populations genetically different from European ancestry have been addressed, being key as the majority of new asthma patients are not white [4]. In epigenetics, several large-scale epigenome-wide association studies (EWAS) have been performed and interaction between environment and epigenetic signatures were of focus.…”
Section: Prefacementioning
confidence: 99%
“…In epigenetics, several large-scale epigenome-wide association studies (EWAS) have been performed and interaction between environment and epigenetic signatures were of focus. Finally, the field of pharmacogenetics has been shown central to understand the susceptibility for and mechanisms of current asthma and allergy therapies, while in parallel, scientific answers to the availability of novel drugs promising individualized therapy are urgently needed [4].…”
Section: Prefacementioning
confidence: 99%
“… 1 In recent years, epigenome-wide association studies (EWAS) have revealed an interaction between epigenetic signatures and allergic diseases, including pediatric asthma. 1 , 2 …”
mentioning
confidence: 99%
“… 1 Children with active IgE-mediated cow’s milk allergy (CMA) showed significantly less FOXP3 TSDR demethylation than those who outgrew CMA or healthy controls, thereby suggesting that FOXP3 TSDR demethylation could serve as a biomarker for oral tolerance. 2 …”
mentioning
confidence: 99%
See 1 more Smart Citation